2020
DOI: 10.1002/rra.3674
|View full text |Cite
|
Sign up to set email alerts
|

Invasive macrophytes induce context‐specific effects on oxygen, pH, and temperature in a hydropeaking reservoir

Abstract: Dense macrophyte beds are known to produce extreme diurnal oxygen and temperature conditions in shallow lakes. However their influences in managed hydropeaking reservoirs has received limited attention. We measured dissolved oxygen, pH and water temperature in the Lake Kar apiro hydroreservoir, northern New Zealand, across a gradient of proportional water-column height occupied by the invasive macrophytes Egeria densa and Ceratophyllum demersum, which dominated in the upperriverine (variable water inflow) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Reservoir management can exacerbate or mitigate the adverse environmental conditions produced by invasive submerged macrophytes near the lake-bed. For example, Moore et al (2020) reported higher reservoir residence time led to reduced water mixing and promoted prolonged anoxic and hypoxic conditions within submerged macrophyte beds in sections of a northern New Zealand hydropeaking reservoir (also the location of the present study in both riverine and lacustrine sections). Accordingly, hydrology (i.e., riverine or lacustrine systems) may partly account for context-specific nature of mussel responses to invasive submerged macrophyte impacts at small spatial scales.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Reservoir management can exacerbate or mitigate the adverse environmental conditions produced by invasive submerged macrophytes near the lake-bed. For example, Moore et al (2020) reported higher reservoir residence time led to reduced water mixing and promoted prolonged anoxic and hypoxic conditions within submerged macrophyte beds in sections of a northern New Zealand hydropeaking reservoir (also the location of the present study in both riverine and lacustrine sections). Accordingly, hydrology (i.e., riverine or lacustrine systems) may partly account for context-specific nature of mussel responses to invasive submerged macrophyte impacts at small spatial scales.…”
Section: Introductionsupporting
confidence: 50%
“…This waterbody, the most downstream in a series of eight reservoirs, has a surface area of 5.4 km 2 , and mean and maximum depths of 11 m and 30.5 m, respectively (Lowe and Green 1987). The reservoir is considered eutrophic (Livingston 1986) with a residence time dependent on inflow: for example, minimum, mean and maximum water inflows of 208, 262 and 320 m 3 s -1 equate to residence times of 3.3, 2.6 and 2.2 days, respectively, given the assumptions of full water column mixing and a lake water volume of 60 x 10 6 m 3 ; Gibbs et al 2015, Moore et al 2020. Karāpiro has an upper-riverine section (hereafter riverine), where discharge from the Arapuni hydropower station produces highly variable flows (as above), and a lower-lacustrine section (hereafter lacustrine) that has a diurnally variable water level related to hydropeaking (see Moore et al 2020).…”
Section: Study Sitementioning
confidence: 99%
“…At other sites, heterotrophic activity, stimulated by temperature increase during summer and autumn, exceeded net oxygen release during the day, that resulting in hypoxia/anoxia events and buildup of CO 2 , CH 4 and NH 4 + in the water column. This observation is recurrent in dense stands formed by invasive macrophytes, where the sedimentation of organic matter generates an elevated benthic BOD during the period of senescence of plants; this implies a permanent DO deficit [ 15 , 31 , 32 ]. In dense hydrophyte stands, DO input from the atmosphere can be limited to the surficial layer of the water column, as long stems constitute a physical barrier, as floating-leaved macrophytes do [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, oxygen dynamics can be altered in densely vegetated stands, such as those dominated by invasive macrophytes: here, due to a fast cycle of growth and decay, fresh organic matter continuously replenishes the organic bulk in the sediment [ 11 ]. In those conditions, elevated biological oxygen demand (BOD) and hypoxia are coupled to accumulation and stratification of nutrients, such as carbon dioxide, methane, ammonium and reactive phosphorous, also during the day [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They play a decisive role in the structure and function of aquatic plant communities in the shallow waters of Erhai Lake, and often cause a simple and unstable community structure in eutrophic waters. In addition, the biomass of C. demersum fluctuates greatly during the year (He et al, 2015), and it declines in autumn (Dong et al, 2019) and then causes dramatic fluctuations in the community structure and composition, weakening the ecological function of the community (Sayer et al, 2010;Moore et al, 2020). Relevant studies have shown that it is reasonable to maintain a low coverage of C. demersum in eutrophic water bodies (Dai et al, 2012).…”
Section: Biodiversity In the Recovered Communitymentioning
confidence: 99%